(untitled) (Quaestiones Disputatae: temas en debate, 2016)
This article describes an experience with the charaterization of mathematical thoughts of the 8th grade students. This is made through the investigation in the classroom for learning irrational numbers. The article is the result of an investigation for the construction of the concept of irrational numbers from the social practices and the interaction in the classroom from the students as well as the teachers. The research is based on group activities, where knowledge is given through interaction in the groups and from the exploration of the surroundings. To do the analysis several activities were made. This was made with a group of students where each one summarized the steps followed to develop the activity. The results obtained were analized highlighting the case stories presented, especially the ones related to irrational numbers. The results allow to define that the group work makes a better construction of learning mathematics.